Combinatorial Optimization of Topological Design in Computer Communication Network - Garba Mohammed, Salisu (2004)
We are living in a new era of information revolution, in which our economy, society, culture and political life are increasingly shaped by computers and communications. The field of telecommunications and networking has, in particular, witnessed more significant developments than many other fields of human knowledge.